1978
DOI: 10.1002/dev.420110108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of visual deprivation in the rat on transfer effects after form discrimination training

Abstract: In 3 experiments the performances of light-reared (LR) and dark-reared (DR) 90-day-old rats were compared on a variety of transfer tests following acquisition of 3 discriminations involving patterns of small squares (dots). Though no significant difference due to rearing condition was found in acquisition of those discriminations consisting of single lines of dots in various orientations, transfer tests did reveal subtle differences in the way LR and DR rats analyze contour information. Significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(20 reference statements)
1
3
0
Order By: Relevance
“…The results of the present study support and extend our previous findings in which the comparisons of visually experienced and inexperienced rats were made under aversive reinforcement and simultaneous presentation conditions and strengthen the idea of a common and selective mammalian response to environmental restriction which transcends differences among species (Tees, 1968(Tees, , 1976Tees, Bruinsma, & Midgley, 1978). In the 1st experiment the results indicated that visually naive animals possess not only the predisposition to isolate and unify a figure from its ground (Hebb, 1937) and the capacity to respond differentially and effectively to vertical, oblique, and horizontal line stimuli, but also the ability to generalize from a limited initial experience with such stimuli to rectangular shapes in different angular orientations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the present study support and extend our previous findings in which the comparisons of visually experienced and inexperienced rats were made under aversive reinforcement and simultaneous presentation conditions and strengthen the idea of a common and selective mammalian response to environmental restriction which transcends differences among species (Tees, 1968(Tees, , 1976Tees, Bruinsma, & Midgley, 1978). In the 1st experiment the results indicated that visually naive animals possess not only the predisposition to isolate and unify a figure from its ground (Hebb, 1937) and the capacity to respond differentially and effectively to vertical, oblique, and horizontal line stimuli, but also the ability to generalize from a limited initial experience with such stimuli to rectangular shapes in different angular orientations.…”
Section: Discussionsupporting
confidence: 91%
“…On the basis of our evidence, we believe that the apparent dissociation between "permanent" effects on neuronal properties and "transient" effects on behavior after deprivation is somewhat of an illusion (Schwartz & Rothblat, 1980;Tees, 1976;Tees & Midgley, 1978). Although attempts to oversimplify the relation between single-unit characteristics such as motion sensitivity, binocularity, and orientational sensitivity, and patterndiscriminative capacities (Barlow, 1972) have helped to confuse the issue of the relative rates of neural and behavioral recovery, behavioral recovery may simply reflect the nature of the behavior and the test.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the capacity to discriminate between patterns such as N vs. X, in which greater integration of visual information over space (and time) is required, clearly depends upon experience. The visually naive, DR rat learns more slowly and learns less about these collections of lines in different orientations than its LR control (Tees, 1972;Tees, Bruinsma, & Midgley, 1978;. Differences between these shapes involve relational properties between sets of linear elements, and it appears that the capacity to perceive even as basic a relationship between linear elements as contour separation is dependent on visual experience for its development (Tees, 1979).…”
mentioning
confidence: 99%